Aplicação da simulação numérica para resolução de problemas de análise de falhas e de mecânica da fratura - Azevedo, Thiago Figueiredo (2014)
Simulation is a virtual tool that assists in the prediction of equipment behavior and it has been currently used for solving mechanical problems even before a physical prototype is tested .Together with the simulation , failure analysis is considered a tool for design optimization . Mechanics fracture, in turn, is a science that seeks to indicate whether a pre-existing crack type defect in the material can lead the component to a catastrophic fracture for normal operating strain. The aim of this work was to analyze numerical simulation importance as a tool for solving failure analysis and fracture mechanics problems in order to obtain quantitative results in response to geometric shapes and complex boundary conditions. Four cases of component failures once made were taken on this work and a complement with numerical simulation was carried out. The obtained results showed that numerical simulation is important in quantitative estimates of in service imposed stresses in the case of complex shape and boundary conditions.